Determinants of Neonatal Mortality in North Shoa Zone, Amhara Regional State, Ethiopia - Kolola, Tufa; Ekubay, Meseret; Tesfa, Endalamaw; Morka, Wogene (PLOS ONE, 2016)
In Ethiopia, neonatal mortality has been declined since the declaration of Millennium Developmental Goals, but the rate was slower since 2006. Thus, this study was designed to assess the determinants of neonatal mortality (NM) in North Shoa Zone. A community based case-control study was conducted on 84 cases and 252 controls. Cases were deceased new-borns within 28 days of birth while controls were infants survived beyond the first 28 days. Data were collected from mothers of the cases and controls using interviewer administered questionnaires. Multivariate analysis was done to examine determinants of NM. Variables significantly associated with NM in bivariate analysis were selected for multivariate analysis. Neonates whose mothers not attended antenatal care (AOR: 3.47; 95%CI: 1.44–8.32), delivered at home (AOR: 2.86; 95%CI: 1.56–5.26), and not received postnatal care services (AOR: 3.09; 95%CI: 1.73–5.51) were more likely to die. The odds of neonatal death was higher among neonates not breastfed within the first hour of delivery than those who breastfed within the first hour of delivery (AOR: 23.48; 95%CI: 8.43–65.37). Likewise, no-colostrum intake was positively associated with neonatal death. Neonates born to mothers who not received or received a single dose of tetanus toxoid injection (TTI) were more likely to experience death than those neonates born to mothers who received two or more doses of TTI (AOR: 2.05; 95%CI: 1.14–3.70). Furthermore, being small in size at birth (AOR: 2.66; 95%CI: 1.33–5.33) and male in sex (AOR: 1.85; 95% CI: 1.06–3.26) were risk factors for NM. In conclusion, neonatal mortality was significantly associated with factors that are modifiable through addressing the continuum-of-care approach in healthcare services in North Shoa. This implies that ensuring a continuity of health care services for maternal and new-borns from antenatal to postnatal care will improve neonatal survival.